Financial development and export diversification in Ethiopia: ARDL approach - Teshager Mazengia Asratie; Misikir Bezabih; Fasika Chekol (Cogent Economics & Finance, 2023)
The main aim of this study was to examine the effect of financial development on Ethiopia's export diversification by applying annual time series data from the period 1980 to 2019. An ARDL estimation technique was employed. In the short run financial development, external debt, and real gross domestic product have a positive significant effect on export diversification. The coefficient of the error correction model is −0.7168 or 71.68% and it is statistically significant that a deviation from long-run equilibrium is not persistent rather it adjusts towards equilibrium at a speed of 71.68% per year. In the long run financial development, trade liberalization, external debt, and real gross domestic product have a positive significant effect on export performance and the bound test confirms the presence of long-run co-integration between variables. It is recommended that government and the national bank of Ethiopia can adjust both saving and lending interest rate policies, providing sufficient loan to export industries that diversify and shifts towards the export of manufactured goods would be indispensable, keeping track of international exchange rate adjustment, liberalization of external trade is crucial and the government of Ethiopia should allocate the borrowed money into high return investment and import substitute goods.
Keywords: 330; ARDL; Ethiopia; export diversification; financial development